Epigenetic emergence: reading for growth in Jane Eyre. Issue 7 (9th August 2019) - Neill, Anna
ABSTRACT: The potential for an intervention by epigenetics into cultural theory and literary analysis has been a topic of recent inquiry from several directions. However, these approaches sometimes too easily align epigenetics with the Lamarckian 'inheritance of acquired characteristics', which presumes the direct influence of environment on the existence of particular traits across generations. This emphasis on environment in turn looks back to eighteenth- and nineteenth-century racial science that attributed degrees of civilisation or savagery to the combined influence of heredity and climate. By instead tracing epigenetics in the older concept of 'epigenesis' from Romantic biology, we can identify the interpretive role of the organism itself in the expression of inherited traits and in the mediation of environmental stimuli. An epigenetic reading of Jane Eyre identifies how Brontë uses the creative agency of the developing body to challenge the 'genetic' and environmental coordinates of racial anthropology. In so doing, she links imperial violence to domestic tyranny and protests against the injustice of both.